Pelatihan Penggunaan Microsoft Office Bagi Siswa MA Nurul Jadid Paiton Probolinggo - Sudriyanto Sudriyanto; Mochammad Faid; Moh Sukron; Ahmad Supriadi (Institut Nalanda, 2023)
This research aims to assess the effectiveness of Microsoft Office training for students of Madrasah Aliyah (MA) Nurul Jadid in Paiton, Probolinggo. The training was chosen due to the importance of enhancing digital literacy and computer skills for students in an era heavily reliant on technology. The community engagement methods employed include lectures, demonstrations, and hands-on exercises conducted by the participants. The research results indicate a positive impact on improving the knowledge and skills of participants in the good category, increasing by 64.42%. However, challenges were observed among participants in the fair and poor categories, experiencing respective declines of 5.45% and 58.96%. These reductions highlight the need to reinforce the program with more varied methods and a personalized approach. Additionally, leveraging technology to facilitate interactive learning is essential to ensure that the benefits of the training can be equally felt by all participants. For further development, program enhancements are necessary to utilize more diverse methods and adopt a personal approach. The integration of technology can be harnessed to create a more interactive learning environment, fostering motivation and ensuring that the training's benefits are equally distributed among all participants. Thus, this research provides valuable insights for future training implementations, enabling a more effective approach to enhancing digital literacy and computer skills for students of Madrasah Aliyah Nurul Jadid in this rapidly advancing technological era.